Prescribing Skills for Undergraduate Medical Students: Time to Redress the Neglect? (Nepal Journal of Epidemiology, 2013)
Challenges in teaching health science students about rational use of medicines include reservations of faculty members about the new learning resources, unfamiliarity with small group teaching, lack of involvement of pharmacologists in teaching therapeutics during the clinical years of training and non-involvement of pharmacists and pharmacologists in patient care activities10. These challenges have to be overcome and a major reorientation and refocusing of pharmacology departments in medical schools towards rational therapeutics may be needed. Modern medical education I feel focuses heavily on diagnosis of disease conditions. Considering the increasing complexity of modern treatment regimens, cost of care and the different stakeholders involved it is time ‘prescribing skills’ receive the attention and resources it richly deserves!DOI: http://dx.doi.org/10.3126/nje.v3i3.9186 Nepal Journal of Epidemiology 2013;3(3): 260-261